2018
DOI: 10.1007/s10068-018-0490-2
|View full text |Cite
|
Sign up to set email alerts
|

Mezcal: indigenous Saccharomyces cerevisiae strains and their potential as starter cultures

Abstract: In this study, 19 indigenous mezcal Saccharomyces cerevisiae strains were screened for their tolerance to grow under different stress conditions and their potential use in fermentation. All strains were able to tolerate pH value of 3, significant levels of glucose (30%), ethanol (12% v/v), and temperature of 37°C. Eleven of them were able to grow in presence of 15% of ethanol, but only CH7 and PA18 strains grew at 42°C. Both were selected for evaluation of their fermentative abilities in maguey juice and in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is reported that the doubling time of Saccharomyces cerevisiae was significantly prolonged under ethanol stress (11% vol), which could be significantly reduced by improving the ethanol tolerance of yeasts [ 44 ]. The indigenous Saccharomyces cerevisiae , such as CHO2 and FF07, isolated from mezcal distilleries in Oaxaca State was able to grow in YEPD medium with 12% vol ethanol after 72 h cultivation [ 45 ]. In this study, CM15 could tolerate 12% vol ethanol stress, and the number of viable cells was about 1.4 × 10 7 CFU/mL after 48 h cultivation ( Figure 4C ), suggesting that CM15 had the excellent tolerance to ethanol stresses.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the doubling time of Saccharomyces cerevisiae was significantly prolonged under ethanol stress (11% vol), which could be significantly reduced by improving the ethanol tolerance of yeasts [ 44 ]. The indigenous Saccharomyces cerevisiae , such as CHO2 and FF07, isolated from mezcal distilleries in Oaxaca State was able to grow in YEPD medium with 12% vol ethanol after 72 h cultivation [ 45 ]. In this study, CM15 could tolerate 12% vol ethanol stress, and the number of viable cells was about 1.4 × 10 7 CFU/mL after 48 h cultivation ( Figure 4C ), suggesting that CM15 had the excellent tolerance to ethanol stresses.…”
Section: Discussionmentioning
confidence: 99%
“…One of the common problems during mezcal production is the presence of residual sugars (Kirchmayr et al ., 2017; Ruiz‐Terán et al ., 2019; Arellano‐Plaza et al ., 2022). Agaves accumulate sugars for 5–15 years, depending on the species (García‐Mendoza et al ., 2017; Arellano‐Plaza et al ., 2022), so it is a considerable loss that these sugars are not fully used.…”
Section: Final Remarksmentioning
confidence: 99%
“…Through this review, we identified names such as tibicos, castaña, xinaiste, jinaiste, zinaiste, el pie, el pie de pulque, asiento, ixquini, semilla, xaxtle, and nancle among the most frequent names that fermenters give to those mixed starter cultures for traditional fermented beverages. The study and characterization of these microbial communities have only been scarcely covered in studies of beverages such as mescal [97,165], pulque [61,166,167], and recently in atole agrio [21]. This technique has been used for years and the methods to prepare them should be considered in further studies.…”
Section: Traditional Knowledge and Microbial Communities In Fermented Beverages: How Do Traditional Fermenters Promote Microbial Reservoimentioning
confidence: 99%
“…The practice of selecting fermentative environments or controlled facilities is common; for instance, people procure fermenting inside the house or special areas to control the external environmental heterogeneity in light incidence, temperature, external contaminants, or pathogens. Moreover, there is a cultural selection of the person who performs the fermentation and the substrate's quality [22,23,97,163,164]. A commonly overlooked aspect is how the microbial communities of starters are selected, prepared, conceived, stored, and used by local fermenters looking for the most favorable composition to improve the quality of their final products.…”
Section: Traditional Knowledge and Microbial Communities In Fermented Beverages: How Do Traditional Fermenters Promote Microbial Reservoimentioning
confidence: 99%